Description of Rhodnius marabaensis sp. N. (Hemiptera, Reduviidade, Triatominae) from Pará State, Brazil - Dos Santos Souza, Eder [UNESP]; Von Atzingen, Noé Carlos Barbosa; Furtado, Maria Betânia; De Oliveira, Jader [UNESP]; Nascimento, Juliana Damieli; Vendrami, Daniel Pagotto; Gardim, Sueli [UNESP]; Da Rosa, João Aristeu [UNESP] (Pensoft Publishers, 2016)
Rhodnius marabaensis sp. n. was collected on 12 May 2014 in the Murumurú Environmental Reserve in the city of Marabá, Pará State, Brazil. This study was based on previous consultation of morphological descriptions of 19 Rhodnius species and compared to the identification key for the genus Rhodnius. The examination included specimens from 18 Rhodnius species held in the Brazilian National and International Triatomine Taxonomy Reference Laboratory in the Oswaldo Cruz Institute in Rio de Janeiro, Brazil. The morphological characteristics of the head, thorax, abdomen, genitalia, and eggs have been determined. Rhodnius prolixus and R. robustus were examined in more detail because the BLAST analysis of a cyt-b sequence shows they are closely related to the new species, which also occurs in the northern region of Brazil. The most notable morphological features that distinguish R. marabaensis sp. n. are the keel-shaped apex of the head, the length of the second segment of the antennae, the shapes of the prosternum, mesosternum and metasternum, the set of spots on the abdomen, the male genitalia, the posterior and ventral surfaces of the external female genitalia, and the morphological characteristics of the eggs. Rhodnius jacundaensis Serra, Serra and Von Atzingen (1980) nomen nudum specimens deposited at the Maraba Cultural Center Foundation - MCCF were examined and considered as a synonym of R. marabaensis sp. n.
Keywords: Amazon; New species; Rhodnius marabaensis sp. n; Triatominae